2003
DOI: 10.1046/j.1472-4669.2003.00009.x
|View full text |Cite
|
Sign up to set email alerts
|

Geomicrobiology of deep‐sea deposits: estimating community diversity from low‐temperature seafloor rocks and minerals

Abstract: The role of deep‐sea microbial communities in the weathering of hydrothermal vent deposits is assessed using mineralogical and molecular biological techniques. The phylogenetic diversity of varied deep‐sea bare rock habitats associated with the oceanic spreading centre at the Juan de Fuca Ridge was accessed using restriction fragment length polymorphism (RFLP) and rDNA sequencing. The mineralogical composition of the deposits used for phylogenetic analysis was determined by X‐ray diffraction in order to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 31 publications
(45 reference statements)
2
51
0
Order By: Relevance
“…Marinobacter aquaeolei VT8 was obtained from the American Type Culture Collection (strain number 700491) and cultivated according to ATCC recommendations. DNA was isolated based on methods adapted from Rogers et al (58).…”
Section: Methodsmentioning
confidence: 99%
“…Marinobacter aquaeolei VT8 was obtained from the American Type Culture Collection (strain number 700491) and cultivated according to ATCC recommendations. DNA was isolated based on methods adapted from Rogers et al (58).…”
Section: Methodsmentioning
confidence: 99%
“…The cell densities on the reacted chimney sulfides were on the order of 10 5 cells mm Ϫ2 . Further studies with sulfides from an active high-temperature chimney revealed that the microbial communities were dominated by bacteria and that diversity levels decreased with increasing oxidation of the chimney material (470). In addition to Zetaproteobacteria, which have been documented on fresher sulfide material, species related to the Gammaproteobacteria grouping of Marinobacter and Halomonas are commonly found in 16S rRNA gene surveys of sulfide materials with a range of oxidation states (134,470).…”
Section: Vol 75 2011 Microbial Ecology Of the Dark Ocean 389mentioning
confidence: 99%
“…Further studies with sulfides from an active high-temperature chimney revealed that the microbial communities were dominated by bacteria and that diversity levels decreased with increasing oxidation of the chimney material (470). In addition to Zetaproteobacteria, which have been documented on fresher sulfide material, species related to the Gammaproteobacteria grouping of Marinobacter and Halomonas are commonly found in 16S rRNA gene surveys of sulfide materials with a range of oxidation states (134,470). More recent analysis of vent chimneys surrounding chloride-enriched or -depleted vents at the Brothers Volcano on the Kermadec Arc revealed that archaeal communities do not appear to vary with chloride influence, being dominated by marine benthic group E, while the bacterial communities do appear to vary with chloride enrichment (534).…”
Section: Vol 75 2011 Microbial Ecology Of the Dark Ocean 389mentioning
confidence: 99%
“…Studies of the role of microbial communities on the weathering of hydrothermal vent deposits at Endeavour show that community diversity decreases with decreasing reactivity of the sulfide component and increasing presence of alteration products (Rogers et al, 2003).…”
Section: Seismicity From 2003 To 2004mentioning
confidence: 99%